Genetic polymorphisms in UDP‐glucuronosyltransferase 1A6 and 1A7 and the risk for benign Warthin's tumors of the parotid gland. (29th July 2015) - Lacko, Martin; Voogd, Adri C.; van de Goor, Rens C.E.; Roelofs, Hennie M.J.; te Morsche, Rene H.M.; Bouvy, Nicole D.; Peters, Wilbert H.M.; Manni, Johannes J.
Abstract: Background: Warthin's tumors of the parotid gland are associated with smoking, whereas pleomorphic adenomas are not. Genetic polymorphisms in biotransformation enzymes, involved in detoxification of toxins and carcinogens in cigarette smoke, might modify the corresponding enzyme activity and influence detoxifying capacity. We hypothesize that these genetic polymorphisms may influence the individual risk for Warthin's tumor, but not for pleomorphic adenomas. Methods: Blood from 146 patients with benign parotid gland tumors and 437 controls were investigated for polymorphisms in several biotransformation enzymes. Based on these polymorphisms, patients and controls were divided according to predicted enzyme activity (low, intermediate, and high). Results: Prevalence of predicted intermediate and high activity UGT1A7 and UGT1A6 genotypes was significantly higher in the patients with Warthin's tumors, but not in patients with pleomorphic adenomas, compared with healthy controls. Conclusion: Predicted intermediate and high activity UGT1A7 and UGT1A6 genotypes are associated with an increased risk for Warthin's tumor. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E717–E723, 2016